On the roles of hunting and habitat size on the extinction of megafauna. (28th February 2017) - Abramson, Guillermo; Laguna, María F.; Kuperman, Marcelo N.; Monjeau, Adrián; Lanata, José L.
Abstract: We study a mechanistic mathematical model of extinction and coexistence in a generic hunter-prey ecosystem. The model represents typical scenarios of human invasion and environmental change, characteristic of the late Pleistocene, concomitant with the extinction of fauna in many regions of the world. As a first approach we focus on a small trophic web of three species, including two herbivores in asymmetric competition, in order to characterize the generic behaviors. Specifically, we use a stochastic dynamical system, allowing the study of the role of fluctuations and spatial correlations. We show that the presence of hunters drives the superior herbivore to extinction even in habitats that would allow coexistence, and even when the pressure of hunting is lower than on the inferior one. The role of system size and fluctuating populations is addressed, showing an ecological meltdown in small systems in the presence of humans. The time to extinction as a function of the system size, as calculated with the model, shows a good agreement with paleontological data. Other findings show the intricate play of the anthropic and environmental factors that may have caused the extinction of megafauna.